2012
DOI: 10.1097/olq.0b013e3182354e81
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sexually Transmitted Infections in HIV-Infected Men During Routine Outpatient Visits in the Netherlands

Abstract: High-risk sexual behavior was very common, and 16% of HIV-infected MSM in HIV care had an asymptomatic STI, mostly anal CT and syphilis. Development of STI screening guidelines is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 40 publications
10
66
8
2
Order By: Relevance
“…In this study, the results showed the prevalence of HIV among Pacific islanders diagnosed with HIV ranges from 1% to 14%. This prevalence is very low as compared with what is observed among MSM [16] but is considered high as it is indicates suboptimum access to health care [17]. However, this is consistent with a study done in Iran (7.14 to 15.95%) in 2010 and South Africa (12.2%) in 2012 [11] [18].…”
Section: Discussionsupporting
confidence: 68%
“…In this study, the results showed the prevalence of HIV among Pacific islanders diagnosed with HIV ranges from 1% to 14%. This prevalence is very low as compared with what is observed among MSM [16] but is considered high as it is indicates suboptimum access to health care [17]. However, this is consistent with a study done in Iran (7.14 to 15.95%) in 2010 and South Africa (12.2%) in 2012 [11] [18].…”
Section: Discussionsupporting
confidence: 68%
“…Overseas, among MSM attending clinics for HIV care, a 13-16% prevalence of STI coinfection has been identified, 158,166,167 with an STI incidence of up to 20 per 100 PY 166,167 and the majority of chlamydia and gonorrhoea being detected at nongenital sites. Independent risk factors for other STIs in these clinic-based studies included younger age, higher numbers of sexual partners, polysubstance use, sharing of sex toys with a sexual partner and enema use.…”
Section: Sti Testing Among Hiv-positive Msmmentioning
confidence: 99%
“…137,158,[165][166][167][168][169] Although HCV has emerged as a STI that is largely confined to HIV-positive MSM, and gonorrhoea and chlamydia are frequently identified, 166 syphilis appears to be the most commonly reported STI coinfection among those with HIV. 159,170 Nonetheless, STI testing rates for nongenital gonorrhoea, chlamydia 171,172 and syphilis 173 in MSM with HIV infection remain below recommended levels.…”
Section: Sti Testing Among Hiv-positive Msmmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Moreover, documentation of condom use often relies on aggregate retrospective self-reports, which have proven vulnerable to distortion, with MSM more commonly underestimating than overestimating unprotected PAI. 19 Additionally, Black MSM's participation in other behavioral practices known or suspected to influence vulnerability to HIV and other STIs, including lubricant use [20][21][22][23][24] and precoital rectal douching or enema use, [25][26][27][28][29][30] has received insufficient attention in the literature.…”
mentioning
confidence: 99%